Assessing Executive Functions in Preschoolers Using Shape School Task - Nieto, Marta; Ros, Laura; Medina, Gloria; Ricarte, Jorge J.; Latorre, José M. (Frontiers in Psychology, 2016)
Over the last two decades, there has been a growing interest in the study of the development of executive functions in preschool children due to their relationship with different cognitive, psychological, social and academic domains. Early detection of individual differences in executive functioning can have major implications for basic and applied research. Consequently, there is a key need for assessment tools adapted to preschool skills: Shape School has been shown to be a suitable task for this purpose. Our study uses Shape School as the main task to analyze development of inhibition, task-switching and working memory in a sample of 304 preschoolers (age range 3.25-6.50 years). Additionally, we include cognitive tasks for the evaluation of verbal variables (vocabulary, word reasoning and short-term memory) and performance variables (picture completion and symbol search), so as to analyze their relationship with executive functions. Our results show age-associated improvements in executive functions and the cognitive variables assessed. Furthermore, correlation analyses reveal positive relationships between executive functions and the other cognitive variables. More specifically, using structural equation modeling and including age direct and indirect effects, our results suggest that executive functions explain to a greater extent performance on verbal and performance tasks. These findings provide further information to support research that considers preschool age to be a crucial period for the development of executive functions and their relationship with other cognitive processes